2017
DOI: 10.1016/j.cels.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Regulation of Protein Turnover in Yeast

Abstract: SUMMARY Protein turnover maintains the recycling needs of the proteome and its malfunction has been linked to aging and age-related diseases. However, not all proteins turnover equally and the factors that contribute to accelerate or slow down turnover are mostly unknown. We measured turnover rates for 3,160 proteins in exponentially growing yeast and analyzed their dependence on physical, functional, and genetic properties. We found that functional characteristics including protein localization, complex membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
136
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(144 citation statements)
references
References 65 publications
8
136
0
Order By: Relevance
“…This is likely due, at least in part, to limited proteome coverage (relative to the protein abundance dataset). However, a recent study also suggested that protein half-life is strongly affected by factors other than sequence characteristics [48], which would likely further dampen trends observed between compositional enrichment and protein half-life. Finally, protein half-life is generally less-conserved than protein abundance [49], perhaps suggesting that specific relationships between conserved sequence features and protein half-life may not be particularly strong.…”
Section: Resultsmentioning
confidence: 99%
“…This is likely due, at least in part, to limited proteome coverage (relative to the protein abundance dataset). However, a recent study also suggested that protein half-life is strongly affected by factors other than sequence characteristics [48], which would likely further dampen trends observed between compositional enrichment and protein half-life. Finally, protein half-life is generally less-conserved than protein abundance [49], perhaps suggesting that specific relationships between conserved sequence features and protein half-life may not be particularly strong.…”
Section: Resultsmentioning
confidence: 99%
“…recently measured protein turnover rates for 3160 proteins in exponentially growing yeast and determined that protein localization, protein complex formation, and connectivity greatly influence protein half‐lives . Assessing PTM profiles, they found that proteins with faster turnover showed higher ubiquitination site occupancy while occupancy for other PTMs was similar between proteins with short or longer half‐lives . In addition, Basisty et al.…”
Section: Protein Aggregation Modifications and Damage Of Aged Proteinsmentioning
confidence: 99%
“…influence protein half-lives. [12] Assessing PTM profiles, they found that proteins with faster turnover showed higher ubiquitination site occupancy while occupancy for other PTMs was similar between proteins with short or longer half-lives. [12] In addition, Basisty et al recently investigated age-related increases in accumulation of long-lived aggregating proteins and correlated their ubiquitination status and insolubility.…”
Section: Protein Aggregation Modifications and Damage Of Aged Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is well established that protein stability and degradation plays an important role in regulated protein turnover during environmental shifts. 16,17 In addition to protein abundance changes, PTMs are well known to regulate protein activity and/or stability during environmental shifts. For example, stress-activated protein kinases coordinate phospho-signal transduction cascades that are largely conserved from yeast through humans.…”
Section: Introductionmentioning
confidence: 99%